Quality and safety of care provided by emergency care practitioners. Issue 4 (22nd April 2011) - O'Hara, Rachel; O'Keeffe, Colin; Mason, Suzanne; Coster, Joanne E; Hutchinson, Allen
Abstract : Background: The emergency care practitioner (ECP) role in the UK health service involves paramedic and nurse practitioners with advanced training to assess and treat minor illness and injury. Available evidence suggests that the introduction of this role has been advantageous in terms of managing an increased demand for emergency care, but there is little evidence regarding the quality and safety implications of ECP schemes. Objectives: The objectives were to compare the quality and safety of care provided by ECPs with non-ECP (eg, paramedic, nurse practitioner) care across three different types of emergency care settings: static services (emergency department, walk-in-centre, minor injury unit); ambulance/care home services (mobile); primary care out of hours services. Methods: A retrospective patient case note review was conducted to compare the quality and safety of care provided by ECPs and non-ECPs across matched sites in three types of emergency care settings. Retrospective assessment of care provided was conducted by experienced clinicians. The study was part of a larger trial evaluating ECP schemes (http://www.controlled-trials.com/ISRCTN22085282 ). Results: Care provided by ECPs was rated significantly higher than that of non-ECPs across some aspects of care. The differences detected, although statistically significant, are small and may not reflect clinical significance. On other aspects of care, ECPs were rated as equal to their non-ECP counterparts. Conclusions: As a minimum, care provided should meet the standards of existing service models and the findings from the study suggest that this is true of ECPs regardless of the service they are operational in.